Strategi Manajemen Risiko Dalam Meningkatkan Return Perusahaan Start-Up Di Era Ekonomi Digital - Hengki Jayeng Pambudi; Yano Andriyanto (Syntax Idea)
In the era of the rapidly developing digital economy, start-up companies face complex challenges related to risk management. These new companies often operate in high-risk environments, including intense competition, rapid technological change, and market uncertainty. The aim of this research is to investigate effective risk management strategies in increasing start-up company returns in the digital economy era. This research will use a qualitative approach. The data collection technique in this research is literature study. The data that has been collected is then analyzed through the stages of data reduction, data presentation and drawing conclusions. The research results show that the main risks faced by start-ups in the digital economy era are technological risk, market risk and financial risk. Effective risk management strategies to increase start-up company returns include appropriate risk identification and assessment, implementation of effective risk mitigation strategies, regular risk monitoring and evaluation. Recommendations for start-ups in developing an effective risk management strategy include building a risk-aware culture within the company, investing time and resources in risk management, and utilizing technology to assist risk management.